Defect-rich MoS2 three-dimensional flower-shaped nano material and preparation method thereof

The synthesis of defect-rich MoS2 three-dimensional flower-like nanomaterials through ultrasonic synergistics without template hydrothermal method was solved, and the problems of slow migration mechanics of Zn2+ and easy collapse of electrode structure in AZIBs were solved, thus achieving electrochemical performance with high capacity and good cycle stability, significantly Improve the energy storage performance of aqueous zinc ion batteries.

CN119240792APending Publication Date: 2025-01-03GUIZHOU MEILING POWER SUPPLY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411333622.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The strong electrostatic interaction between Zn2+ and the matrix material in existing aqueous zinc ion batteries (AZIBs) leads to slow migration mechanics of Zn2+, easy collapse of electrode structure, affecting energy storage performance, and existing MoS2 materials are easily damaged during charging and discharging. , affects circulation stability.

Method used

Defect-rich MoS2 three-dimensional flower-like nanomaterials were synthesized through ultrasonic synergistics without template hydrothermal method, and MoS2 nanoflowers were reduced by NaBH4 to form 1T/2H coexisting MoS2 nanoflowers, introducing sulfur defects and edge sites, and improving the Zn2+ embedding and diffusion rate , optimize electrochemical properties.

Benefits of technology

The high reversible capacity, good rate performance and excellent cycle stability of MoS2 in AZIBs was achieved, and the discharge specific capacity reached 258.3mAh·g-1. The capacity remained 91.3% after 1500 cycles, and the power density was 73.7W·kg–1. Significantly improves electrochemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240792A_ABST
    Figure CN119240792A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nano materials, in particular to a defect-rich MoS2 three-dimensional flower-shaped nano material and a preparation method thereof.According to the defect-rich MoS2 three-dimensional flower-shaped nano material and the preparation method thereof, a 1T / 2H coexisting MoS2 nano flower formed by assembling nanosheets is synthesized through an ultrasonic cooperation template-free hydrothermal method, and the MoS2 nano flower is reduced through NaBH4 at the room temperature to synthesize a defect-rich MoS2-x nano sheet flower-shaped structure. On one hand, due to the flower-shaped 1T / 2H nanostructure, the MoS2 nanosheet has relatively high conductivity in a 1T phase and has good stability in a 2H phase; on the other hand, the defect engineering strategy can effectively construct charge redistribution on the MoS2-x nanosheet rich in sulfur defects, the intrinsic conductivity is further improved, electrochemical active sites are increased, the diffusion rate of Zn < 2 + > is increased, and the electrochemical performance is optimized. Research results show that the defect-rich MoS2-x nanosheet obtains the specific discharge capacity of 258.3 mAh.g <-1 > at 0.1 A.g <-1 >, good rate capability and excellent cycling stability (the capacity is kept at 91.3% after 1500 times of cycling).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanomaterials, in particular to a defect-rich MoS2 three-dimensional flower-shaped nanomaterial and a preparation method thereof. Background Art

[0002] Finding efficient electrochemical energy storage devices is one of the important ways to meet the current energy needs. Among them, aqueous zinc-ion batteries (AZIBs) with good compatibility with aqueous electrolytes, non-toxicity, and low cost of zinc negative electrodes are considered to have high application value and development prospects in large-scale energy storage. 2+ The strong electrostatic interaction between Zn and the matrix material has always been a problem that has plagued the development of AZIBs, which has led to 2+ The migration kinetics are slow, with repeated insertion and removal of Zn 2+ The rear electrode structure collapsed seriously. Therefore, it is necessary to explore suitable Zn 2+ Cathode materials with high efficiency, fast speed and stable storage are one of the keys to promote the development of AZIBs.

[0003] As a promising molybdenum-based material, MoS2 with a graphene-like layered structure has attracted much attention. In the MoS2 molecule, the covalently bonded S-Mo-S layers have weak van der Waals interactions, which is conducive to the embedding of foreign guests therein. Due to the anisotropic structure, MoS2 easily forms a two-dimensional morphology, providing a large surface area and permeation channels for ion adsorption and transport, making it a very promising battery electrode material. Ultrathin two-dimensional nanosheets can self-assemble into various three-dimensional network structures, thereby promoting rapid electron transfer and ion transport, and improving the effective utilization of MoS2 in electrochemical reactions. However, due to the weak van der Waals interlayer structure, the original MoS2 crystal structure without further modification is prone to collapse, and severe volume expansion can cause battery damage, thereby affecting the discharge capacity and cycle stability during the charge and discharge process. Therefore, it is necessary to develop new synthetic strategies to prepare Zn 2+ Reversibly intercalated MoS2 materials.

[0004] Generally, as the cathode material of AZIBs, MoS2 mostly adopts interlayer engineering and defect engineering strategies to enhance the Zn 2+ In 2019, Liang et al. converted inactive MoS2 into efficient Zn by adjusting the intercalation energy. 2+ Storage materials, achieving 232mAh g -1 The high capacity of Zn MoS2 is 10 times that of the original MoS2. In the same year, Xu et al. predicted through density functional theory calculations that edge and sulfur defects can serve as Zn 2+Preferentially embedded sites can achieve a larger capacity compared to pure MoS2. Several methods for synthesizing defect-rich MoS2 with highly active edge sites have been reported. In 2013, Xie et al. synthesized defect-rich MoS2 with exposed active edge sites by adjusting the amount of thiourea in a solvothermal process. In 2017, Tsai et al. used electrochemical desulfurization to generate S defects on the MoS2 basal plane and controlled the concentration of S defects by changing the applied desulfurization voltage.

[0005] Among these strategies, few researchers have paid attention to the effects of sulfur defects on regulating electronic structure and nanosheet structure design on electrochemical performance. Therefore, finding a strategy to improve the zinc storage performance of MoS2 in AZIBs by introducing sulfur defects to regulate electronic structure and nanosheet structure design through ultrasound-assisted template-free hydrothermal method is the current key research direction. Summary of the invention

[0006] In order to solve the above technical problems existing in the prior art, the present invention provides a defect-rich MoS2 three-dimensional flower-shaped nanomaterial and a preparation method thereof, which is specifically achieved through the following technical scheme.

[0007] A method for preparing defect-rich MoS2 three-dimensional flower-like nanomaterials, synthesizing 1T / 2H coexisting MoS2 nanoflowers assembled from nanosheets by ultrasound-assisted template-free hydrothermal method, and synthesizing defect-rich MoS by reducing MoS2 nanoflowers with NaBH4 at room temperature 2﹣x Nanosheet flower-like structure.

[0008] Furthermore, the method comprises the following steps:

[0009] (1) Take NH2CSNH2 and (NH4)6Mo7O respectively 24 4H2O was dissolved in distilled water and stirred under ultrasonic cavitation to obtain solution A;

[0010] (2) Transferring the solution A obtained in (1) to a stainless steel high-pressure reactor for reaction; cooling to room temperature after the reaction is completed, taking out, filtering, washing, and drying to obtain black nanoflower MoS2; and cooling naturally;

[0011] (3) Disperse the nanoflower MoS2 obtained in (2) into an ethanol solution, add NaBH4, obtain a precipitate, remove it, filter it, wash it, and dry it to obtain defect-rich MoS 2﹣x Nanosheet flower-like structural materials.

[0012] Furthermore, in step (1), 10-20 mmol NH2CSNH2 and 0.3-0.7 mmol (NH4)6Mo7O are respectively weighed. 24 Dissolve 4H2O in 40-80 mL of distilled water.

[0013] Furthermore, the stirring in step (1) is magnetic stirring at a stirring speed of 300 to 600 rpm for 40 to 80 min.

[0014] Furthermore, the reaction in step (2) is carried out by heating at 110-220° C. for 16-32 h at a heating rate of 8-12° C. / min.

[0015] Furthermore, the washing in steps (2) and (3) is performed with distilled water and ethanol respectively, preferably three times each.

[0016] Furthermore, the drying in steps (2) and (3) is performed at 40 to 80° C. for 8 to 16 hours:

[0017] Furthermore, the nanoflower MoS2 in step (3) is dispersed into an ethanol solution, specifically, the nanoflower MoS2 is ultrasonically dispersed into 25-50 ml of ethanol solution and stirred for 20-40 minutes.

[0018] Furthermore, in the step (3), the addition of NaBH4 is performed by slowly adding 0.006 to 0.014 mol of NaBH4 under stirring, and then continuously stirring for 80 to 160 minutes.

[0019] The defect-rich MoS2 three-dimensional flower-shaped nanomaterial is prepared by the above-mentioned method for preparing the defect-rich MoS2 three-dimensional flower-shaped nanomaterial.

[0020] Compared with the prior art, the technical effects created by the present invention are embodied in:

[0021] (1) The present invention synthesized 1T / 2H coexisting MoS2 nanoflowers assembled from nanosheets by ultrasound-assisted template-free hydrothermal method, and synthesized defect-rich MoS2 nanoflowers by reducing MoS2 nanoflowers with NaBH4 at room temperature. 2﹣x On the one hand, the flower-like 1T / 2H nanostructure makes the MoS2 nanosheets have high conductivity in the 1T phase and good stability in the 2H phase; on the other hand, the defect engineering strategy can effectively construct MoS2 rich in sulfur defects. 2﹣x The charge redistribution on the nanosheets further improves the intrinsic conductivity and increases the electrochemical active sites, thereby increasing the Zn 2+ The results show that defect-rich MoS 2﹣x Nanosheets at 0.1A·g -1 Obtain 258.3 mAh g -1 It has high discharge capacity, good rate performance and excellent cycle stability (capacity retention of 91.3% after 1500 cycles).

[0022] (2) The present invention successfully prepared MoS nanosheets self-assembled into three-dimensional flower-like nanostructures by using ultrasound-assisted template-free hydrothermal method. 2﹣x After treatment with NaBH4 ethanol solution, some S atoms on MoS2 are removed, resulting in sulfur defects regulating the electronic structure and the formation of nanosheet structures. This improves the zinc storage performance of MoS2 in AZIBs. The main advantages are as follows: MoS 2﹣x There are a large number of edge sites, sulfur defects and wider interlayer spacing. These features make Zn 2+ It is easier to insert and greatly enhance the reversible capacity of the electrode. Thanks to the above synergistic effect, MoS rich in sulfur defects 2﹣x Its specific capacity, battery efficiency, rate performance and reversibility are significantly improved, showing excellent electrochemical performance, mainly including the –1 258.3mAh·g -1 High reversible capacity and power density of 73.7 W kg –1 141.9Wh·kg –1 High energy density and 3A·g -1 At a current density of 1500, the defect-rich MoS 2﹣x The electrode still has a capacity retention rate of 91.3%. These excellent electrochemical properties are related to the generation of nanoflowers by ultrasound-assisted template-free hydrothermal method, while the reduction of NaBH4 ensures the defect-rich MoS 2﹣x The flower-like structure of nanosheets and the large interlayer spacing make MoS2 nanosheets a promising candidate as cathode materials for AZIBs. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is the original MoS2 and MoS 2﹣x Flowchart of the synthesis steps of experimental samples.

[0024] Figure 2 is (ac)MoS2, (df)MoS 2﹣x SEM image of the sample; (g) TEM image of MoS2; MoS 2﹣x (h) TEM image, (i) HRTEM image and (j) corresponding elemental mapping.

[0025] Figure 3 (a) XRD pattern, (b) Raman spectrum, (c) Mo 3d and (d) S2p single spectra of the sample.

[0026] Figure 4 It is the N2 adsorption-desorption isotherm curve and BJH pore size distribution diagram.

[0027] Figure 5 MoS2 and MoS 2﹣x (a) At 0.4 mV·s -1 CV curves under (a) and (b) at 0.1A·g –1 GCD diagram under (c) MoS 2﹣x In 0.1-5A·g -1 GCD diagram of MoS2 and MoS 2﹣x (d) Rate performance, (e) Cycling performance and (f) Ragone plot of power density vs. energy density compared with other different electrochemical energy storage devices. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further defined below in conjunction with specific implementation methods, but the scope of protection required is not limited to the description.

[0029] Embodiment 1:

[0030] (1) Take 15 mmol NH2CSNH2 and 0.5 mmol (NH4)6Mo7O 24 4H2O was dissolved in 60 mL of distilled water and magnetically stirred at 500 rpm for 60 min under ultrasonic cavitation to obtain solution A;

[0031] (2) The solution A obtained in (1) was transferred to a stainless steel autoclave and heated at 160°C for 24 h at a heating rate of 10°C / min. After the reaction was completed, it was naturally cooled to room temperature, taken out and filtered, washed three times with distilled water and ethanol respectively, and dried at 60°C for 12 h to obtain black nanoflower MoS2.

[0032] Embodiment 2:

[0033] (1) Take 15 mmol NH2CSNH2 and 0.5 mmol (NH4)6Mo7O 24 4H2O was dissolved in 60 mL of distilled water and magnetically stirred at 500 rpm for 60 min under ultrasonic cavitation to obtain solution A;

[0034] (2) The solution A obtained in (1) was transferred to a stainless steel autoclave and heated at 160°C for 24 h at a heating rate of 10°C / min. After the reaction was completed, it was naturally cooled to room temperature, taken out and filtered, washed three times with distilled water and ethanol respectively, and dried at 60°C for 12 h to obtain black nanoflower MoS2.

[0035] (3) The nanoflower MoS2 obtained in (2) was ultrasonically dispersed in 40 ml of ethanol solution and stirred for 30 min. Then, 0.01 mol of NaBH4 was slowly added under stirring, and then stirred for 120 min to obtain a precipitate. The precipitate was taken out and filtered, and washed three times with distilled water and ethanol respectively, and dried at 60 ° C for 12 h to obtain defect-rich MoS 2﹣x Nanosheet flower-like structure material. After being treated with NaBH4 ethanol solution, some S atoms on MoS2 were removed, resulting in the generation of sulfur defects.

[0036] Fabrication of working electrode:

[0037] (1) Add active material: conductive agent: binder in a mass ratio of 7:2:1 into NMP and grind thoroughly in a mortar until a slurry without particles is obtained;

[0038] (2) The slurry obtained in (1) is uniformly coated on a clean titanium foil, which is then placed in a vacuum drying oven at 60° C. for 12 h to obtain an electrode;

[0039] (3) The electrode prepared in (2) was used as the positive electrode, zinc foil as the negative electrode, 3MZn(CF3SO3)2 as the electrolyte, and the diaphragm was glass cellulose filter paper to assemble AZIBs. 2﹣x Characterization of physical and chemical properties of three-dimensional flower-like nanomaterials

[0040] (1) SEM and TEM analysis

[0041] MoS2 and MoS were analyzed by SEM. 2﹣x The appearance of. Figure 2 (ac) It can be clearly observed that MoS2 is a flower-like microsphere formed by stacking nanosheets with an average diameter of about 500nm. After treatment with NaBH4, the distance between nanosheets increases and the nanosheets become irregular and wrinkled ( Figure 2 (df)).MoS 2﹣x Instead of a complete nanoflower-like microsphere, the petal-like structure gradually disperses to form a porous network structure. The change in morphology is because the treatment of the original MoS2 with NaBH4 destroys its complete structure. According to literature reports, the distance between the nanosheets increases, which may provide abundant sites for redox reactions and insertion / deinsertion processes. In addition, the relatively small size should help shorten the Zn 2+ diffusion length, thus promoting the electrochemical reaction.

[0042] Figure 2 (g) and Figure 2 (h) is MoS2 and MoS 2﹣xTEM images of MoS2 and MoS4 show that both are flower-like nanostructures composed of stacked nanosheets with lateral sizes ranging from hundreds of nanometers to micrometers. These results are consistent with the SEM images. 2﹣x The microstructure of Figure 2 (i) shows that MoS 2﹣x The interlayer distance is about 0.98nm. In addition, some of them are along the MoS 2﹣x The lattice fringes at the curled edges are discontinuous, with many dislocations and deformations, proving that there are lattice distortions and atomic defects. These additional defects will add more edge active sites. 2﹣x TEM images and corresponding elemental maps of elemental distribution Figure 2 (j) It is judged that Mo and S elements exist and are distributed on the entire surface of the nanoflower.

[0043] (2) XRD, Ranman, XPS and ICP analysis

[0044] Figure 3 (a) shows the original MoS2 and MoS 2﹣x XRD spectra. It can be observed that the diffraction peak corresponding to the (002) plane of MoS2 in the two samples has a lower displacement angle than the diffraction peak of the standard pattern of MoS2 (JCPDS No.37-1492). This indicates that the interlayer spacing of the MoS2 (002) plane has increased. Diffraction peaks with a diploid relationship appear, which is consistent with the XRD spectrum of the 1T phase MoS2 material. At the same time, MoS 2﹣x The (002) characteristic peak of MoS2 moves to a lower angle relative to that of MoS2. According to the Bragg equation, the MoS 2﹣x The lattice spacing of the (002) crystal plane is about 0.98nm, which is larger than the lattice spacing of the original MoS2 (0.94nm). This increase in interlayer spacing may be due to the large amount of H2 produced after the addition of NaBH4 and entering the MoS2 interlayer. The interlayer spacing directly affects the Zn 2+ The increase in interlayer diffusion and interlayer spacing during the electrochemical process fundamentally improves the ion diffusion rate and structural stability, reduces the volume expansion rate during the electrochemical process, and ultimately improves the rate and cycle stability of AZIBs.

[0045] A of MoS2 1g corresponds to the opposite vibration mode of the outer S atoms in a unit cell, and It reflects the vibration mode of the middle Mo atom and the two S atoms in the layer in the opposite direction. 2﹣x The Raman diagram is as follows Figure 3 As shown in (b), MoS 2﹣x of Peak and A1g The shortened interval between the peaks indicates that the interaction between adjacent MoS2 layers is weakened. The ratio of the peak intensities of the two can reflect the edge exposure of MoS2, and the smaller the value, the higher the edge exposure. The increase in exposed active edge sites is related to the generation of defect-rich structures, which produce more coordinated unsaturated edge sites. Compared with pristine MoS2, MoS 2﹣x Mo3d 3 / 2 、Mo 3d 5 / 2 and S2p 3 / 2 , 2p 1 / 2 are transferred to lower binding energies ( Figure 3 (cd)). According to previous studies, this reflects the increase in electron density around the Mo and S sites, which is caused by the presence of sulfur defects. MoS 2﹣x Mo 3d 3 / 2 and Mo 3d 5 / 2 There are two main peaks at 232.0eV and 228.7eV, indicating that Mo 4+ The dominant position in the material. The weak peak is located at 236.1eV, which is Mo 6+ Mo 3d 3 / 2 , indicating that the Mo 4+ A small amount of oxidation occurred. In addition, the peak at 226.0 eV represents S2s. 2﹣x The Mo3d peak fitting results in 1T phase MoS 2﹣x The Mo 3d bond energy of the 1T phase MoS is about 0.8 eV lower than that of the 2H phase. Similarly, after peak fitting of S2p, we get 2﹣x The S2p bond energy of the 2H phase is about 0.8 eV lower than the Mo 3d bond energy of the 2H phase, which is consistent with the results reported in the previous literature. The XPS fitting results show that both are composed of 1T and 2H phases. In order to further confirm the existence of defects, inductively coupled plasma (ICP-OES) testing was used to obtain MoS 2﹣x The exact atomic ratio of S / Mo is 1.88.

[0046] (3)BET

[0047] In addition, we determined the defective MoS 2﹣x The specific surface area and pore size distribution of the product. Figure 4 It can be seen that MoS 2﹣x It has obvious type IV isotherm and H3 type hysteresis loop, which is characterized by MoS 2﹣x The results show that MoS 2﹣xThe average pore size is about 22.8nm, with a mesoporous structure. The obtained mesoporous nanostructure provides abundant microchannels and active sites for the entry of electrolytes and the occurrence of redox reactions, which promotes the electrochemical process from a kinetic perspective.

[0048] Electrochemical performance test

[0049] Figure 5 (a) The product is used as an electrode in the voltage range of 0.2-1.3 V when the scan rate is 0.4 mV·s -1 CV curve diagram below. Compared with the original MoS2, MoS 2﹣x The larger reduction and oxidation peaks can produce larger current density, which may indicate that MoS with rich defects and extended layered structure 2﹣x Has a larger capacity and can hold more Zn 2+ Embedding. Figure 5 (b) shows that when the current density is 0.1A·g -1 , MoS 2﹣x With about 258.3mAh·g -1 The discharge capacity of MoS2 is 1.8 times that of the original MoS2. When MoS2 is used in a battery system with a single electron as a carrier, the theoretical capacity is about 670 mAh g -1 According to electrochemical analysis, each MoS 2﹣x Can transfer 0.8 Zn 2+ . Figure 5 (c) MoS 2﹣x GCD curves at different current densities show that each curve exhibits a similar shape, indicating that MoS 2﹣x Can maintain good Zn in aqueous electrolyte environment 2+ Intercalation / deintercalation behavior. Figure 5 (d) describes the rate performance of the two cathode materials. It can be seen that the current density is 0.1, 0.2, 0.5, 1.0, 2.0 and 5.0 A·g -1 When the discharge capacity of the original Mo S2 is only 149.7, 129.0, 108.2, 89.7, 69.8, and 47.4 mA h g -1 However, MoS 2﹣x At the same current density, the specific capacities output were 258.3, 234.0, 203.4, 180.7, 161.0 and 135.5 mAh g -1 , and when the current density returns to 0.1A·g -1 When the specific capacity can be restored to 243.9 mAh g -1 , and the corresponding capacity retention rate is 94.1%. MoS 2﹣xThe specific capacity at each current density is relatively stable. With the increase of current density, the discharge specific capacity shows a gentle step-type distribution, which reflects the excellent capacity recovery and fast reaction kinetics, and verifies that the performance of MoS2 can be improved by rich defect engineering. Compared with other advanced positive electrode materials for ZIBs, it has better zinc storage performance. Table 1 compares the zinc storage performance with other MoS2 nanomaterials.

[0050] To further demonstrate its excellent working life, pristine MoS2 and MoS 2﹣x In 3A·g -1 Cycling performance after 1500 cycles. Figure 5 (e) It can be seen that MoS 2﹣x The initial capacity is 91.1 mAh g -1 After 1500 cycles, the capacity remained at 83.1 mAh g -1 , the capacity retention rate is 91.3%, the coulombic efficiency is close to 100%, and it shows excellent cycling stability at high charge and discharge rates. It is worth noting that in the first 200 cycles, the capacity increases slightly, reflecting the release of effective capacity during the electrode activation process. This is due to the Zn 2+ After repeated embedding and de-embedding, the ion diffusion channel gradually becomes smooth, the structural mechanics gradually becomes stable, and the electrolyte penetration becomes more sufficient. Figure 5 (f) is MoS 2﹣x Ragone plots of energy density and power density of pristine MoS2 cathode materials, showing that MoS 2﹣x / / Zn at 70.4W·kg -1 When the power density is 141.9Wh·kg -1 (0.1A g -1 ) has an energy density of 2763.8 W kg -1 At a high power density of 73.7Wh kg -1 (5A·g -1 ) energy density. While MoS2 / / Zn has an energy density of 85.5W·kg -1 The power density is 82.4Wh kg -1 The energy density is 1675.9W·kg -1 At a high power density of only 26.1Wh·kg -1 (5A·g -1 ) energy density. In contrast, it was found that MoS 2﹣x / / Zn can provide high energy density while maintaining high power density.

[0051] Table 1 Comparison of zinc storage performance with other MoS2 nanomaterials

[0052]

[0053] Finally, it should be pointed out that the above embodiments are only representative examples of the present invention. Obviously, the technical solution of the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by ordinary technicians in this field should be considered as the protection scope of the present invention.

Claims

1. A method for preparing defect-rich MoS2 three-dimensional flower-shaped nanomaterial, characterized in that: MoS2 nanoflowers with 1T / 2H coexistence assembled from nanosheets were synthesized by ultrasound-assisted template-free hydrothermal method, and defect-rich MoS was synthesized by reducing MoS2 nanoflowers with NaBH4 at room temperature. 2﹣x Nanosheet flower-like structure.

2. The method for preparing defect-rich MoS2 three-dimensional flower-shaped nanomaterial according to claim 1, characterized in that: The following steps are involved: (1) Take NH2CSNH2 and (NH4)6Mo7O respectively 24 4H2O was dissolved in distilled water and stirred under ultrasonic cavitation to obtain solution A; (2) transferring the solution A obtained in (1) to a stainless steel high-pressure reactor for reaction; after the reaction is completed, cooling to room temperature, taking out, filtering, washing, and drying to obtain black nanoflower MoS2; (3) Disperse the nanoflower MoS2 obtained in (2) into an ethanol solution, add NaBH4, obtain a precipitate, remove it, filter it, wash it, and dry it to obtain defect-rich MoS 2﹣x Nanosheet flower-like structural materials.

3. The method for preparing defect-rich MoS2 three-dimensional flower-shaped nanomaterial according to claim 2, characterized in that: The step (1) is to weigh 10-20 mmol NH2CSNH2 and 0.3-0.7 mmol (NH4)6Mo7O 24 Dissolve 4H2O in 40-80 mL of distilled water.

4. The method for preparing defect-rich MoS2 three-dimensional flower-shaped nanomaterial according to claim 2, characterized in that: The stirring in step (1) is magnetic stirring at a stirring speed of 300 to 600 rpm for 40 to 80 min.

5. The method for preparing defect-rich MoS2 three-dimensional flower-shaped nanomaterial according to claim 1, characterized in that: The reaction in step (2) is carried out by heating at 110-220° C. for 16-32 hours at a heating rate of 8-12° C. / min.

6. The method for preparing defect-rich MoS2 three-dimensional flower-shaped nanomaterial according to claim 1, characterized in that: The washing in steps (2) and (3) is washing with distilled water and ethanol respectively.

7. The method for preparing defect-rich MoS2 three-dimensional flower-shaped nanomaterial according to claim 1, characterized in that: The drying in steps (2) and (3) is performed at 40 to 80° C. for 8 to 16 hours.

8. The method for preparing defect-rich MoS2 three-dimensional flower-shaped nanomaterial according to claim 1, characterized in that: The nanoflower MoS2 in the step (3) is dispersed into an ethanol solution, specifically, the nanoflower MoS2 is ultrasonically dispersed into 25-50 ml of ethanol solution and stirred for 20-40 minutes.

9. The method for preparing defect-rich MoS2 three-dimensional flower-shaped nanomaterial according to claim 1, characterized in that: The addition of NaBH4 in step (3) is to slowly add 0.006 to 0.014 mol of NaBH4 under stirring, and then continue stirring for 80 to 160 minutes.

10. The defect-rich MoS2 three-dimensional flower-shaped nanomaterial prepared by the method for preparing the defect-rich MoS2 three-dimensional flower-shaped nanomaterial according to claim 1.